Transition Risks of Climate Change: An Analysis of Greenhouse Gas Emissions in Croatia and the Euro Area - Srdelic, Leonarda (Oeconomica Jadertina, 2024)
This paper analyses data from the United Nations Framework Convention on Climate Change (UNFCCC) on greenhouse gas emissions. The aim is to identify the sectors that contribute most to climate change, assess their effectiveness in implementing emission reduction policies, and achieve sustainable development goals. Based on the analysis, it is clear that the energy, transport, and industrial processes sectors are key in the context of sensitivity to EU climate policies. In contrast, the Land Use, Land-Use Change and Forestry sector stands out as offering unique opportunities for mitigating climate change through carbon sequestration activities and thereby achieving climate neutrality.